Polymeric Compositions on the Base of Acrylic Acid and Bentonite Clay: Experimental Investigation - M. A. Makhkamov; M. G. Mukhamediev (Challenges and Advances in Chemical Science Vol. 8, 2022)
Some peculiarities of obtaining composition hydrogels (CH) on the basis of cross-linked polyacrylic acid (PAAc) and bentonite clay (BC) were investigated in this study. Optical microscopy and X-ray diffraction have revealed that in CHs, the crystalline structure of montmorillonite has been destroyed due to the penetrative of polymeric macromolecules between bundle layers, resulting in a uniform homogeneous structure. The kinetics of swelling of obtained CH in water were studied, and it was discovered that they have a high sorption ability to water over a wide pH range. The statistical method was used to investigate the sorption of methylene blue (MB) by gels from water solutions. The sorption ability of CHs was found to be greater than that of hydrogels on a PAAc base. Sorption of MB has increased with increasing medium temperature, and as a result, bonding of MB by CHs has occurred due to chemisorption.